1988
DOI: 10.1111/j.1476-5381.1988.tb11449.x
|View full text |Cite
|
Sign up to set email alerts
|

Activities of octopamine and synephrine stereoisomers on α‐adrenoceptors

Abstract: 1 The activities of the (-)-and (+ )-forms of m-and p-octopamine and m-and p-synephrine on a,-adrenoceptors from rat aorta and anococcygeus and a2-adrenoceptors from rabbit saphenous vein were compared with those of noradrenaline (NA).2 The rank order of potency of the (-)-forms on cx,-adrenoceptors from rat aorta and a2-adrenoceptors was NA > m-octopamine = m-synephrine > p-octopamine = p-synephrine. The two m-compounds were 6 fold less active than NA on x,-adrenoceptors from rat aorta and 150 fold less activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 28 publications
2
60
2
Order By: Relevance
“…Similar to the cavernous artery, the potency order of antagonists pointed to a 1A -AR, but the low Schild slopes did not confirm competitive antagonism. Both NA, and to a lesser extent, PE (Brown et al, 1988), at high concentrations can act at a 2 -ARs. Rabbit penile tissue, specifically corpus cavernosum strips (Gupta et al, 1998), has been demonstrated to possess functional post-junctional a 2 -ARs in addition to the predominant a 1 -ARs.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to the cavernous artery, the potency order of antagonists pointed to a 1A -AR, but the low Schild slopes did not confirm competitive antagonism. Both NA, and to a lesser extent, PE (Brown et al, 1988), at high concentrations can act at a 2 -ARs. Rabbit penile tissue, specifically corpus cavernosum strips (Gupta et al, 1998), has been demonstrated to possess functional post-junctional a 2 -ARs in addition to the predominant a 1 -ARs.…”
Section: Discussionmentioning
confidence: 97%
“…[1-14 C]oleic acid (56 mCi/mmol) and [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]octanoic acid (50 mCi/mmol).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown, for example, that p-synephrine binds to serotoninergic receptors [4]. Likewise, an action of p-synephrine via adrenergic receptors has been documented [5] [6] [7]. Acute oral administration of elevated doses of a C. aurantium extract or psynephrine produced reversible toxic effects, probably due to unspecific adrenergic stimulation [3].…”
Section: Introductionmentioning
confidence: 99%
“…The adrenergic activities of (+)-isomers are at least 1 to 2-fold lower than those of their (-)-counterparts. The activities of the respective synephrine and octopamine isomers towards α-adrenoceptors are about 1 or 2 orders of magnitude higher compared to their activities towards β-adrenoceptors (Jordan et al 1987, Brown et al 1988, Evans et al 1988, Pellati et al 2002, Pellati & Benvenuti 2007, Avula et al 2005.…”
Section: Proposed Uses and Use Levelsmentioning
confidence: 99%
“…aurantium L.). Moreover, potential additive effects of the p-synephrine, m-synephrine and/or octopamine are to be considered in such cases (Jordan et al 1987, Brown et al 1988, Evans et al 1988, NTP/NIEHS 2004, Blumenthal 2005). …”
Section: Specificationsmentioning
confidence: 99%